Singapore's Transition to Innovation-based Economic Growth: Infrastructure, Institutions and Government's Role - KOH, Winston T. H. (Institutional Knowledge at Singapore Management University, 2006)
Technological progress and innovation plays a central role in a country's economic progress. As an economy advances to the global technological frontier and narrows the technological gap, an innovation-based growth strategy that focuses on investments in R&D and technology creation offers the greatest potential for economic growth. In this paper, we discuss the requirements for a successful transition, in terms of changes to the technology infrastructure, economic institutions and the incentives' structure. This paper outlines the efforts made by Singapore to re-make itself as an innovation-based economy, and the challenges faced by the government in transforming the nation's infrastructure and institutions to develop innovation capabilities and encourage entrepreneurship. [ABSTRACT FROM AUTHOR]